Reefs of rubbish: the ecological implications of anthropogenic litter in streams - Wilson, Hazel (2021)
Anthropogenic litter (solid manufactured waste) is a significant and increasing problem worldwide. However, despite emerging evidence of the prevalence of litter in rivers, most research has focused on the marine environment. Anthropogenic litter has been shown to have a variety of environmental impacts in aquatic systems, but its consequences for rivers are poorly understood. This thesis aimed to address this by investigating the characteristics and ecological impacts of litter in rivers. I undertook field surveys and in situ experiments to determine how macroinvertebrates and fish are affected by riverine litter. First, in a survey of small and heavily managed UK rivers, I found that anthropogenic litter density across a range of small and heavily managed UK rivers ranged from 0 to 8.7 items m-2. This density is comparable to that reported in other aquatic systems, confirming that rivers contain considerable quantities of litter and demonstrating the need for increased research into litter in rivers. Plastic was the most common litter material, but its dominance was less than has been found in marine systems or on river banks. Thus, excluding non-plastic materials, like glass and metal, from riverine litter research risks omitting a significant proportion of anthropogenic litter from investigation. This study also found a positive correlation between litter density and macroinvertebrate diversity across rivers. This surprising result suggested that anthropogenic litter could increase the diversity of available habitat, especially in managed rivers that are otherwise scarce in habitat diversity. This finding was supported by the results of a second investigation comparing the macroinvertebrate communities inhabiting litter and natural mineral substrates (rocks); the dominant natural substrate in the sampled rivers. It found that communities on litter were consistently more diverse than rock equivalents, reflecting the greater surface complexity of the litter. Results also suggested that small-scale differences in the physical properties of litter types and rocks cause the different substrates to support distinct macroinvertebrate communities. In particular, flexible plastic and fabric items were inhabited by macroinvertebrate taxa that would typically live on macrophytes, suggesting that these types of litter items can mimic the structure of plants. Anthropogenic litter, especially large litter items, may affect more than just the organisms which inhabit its surface. By altering local habitat conditions it could impact biota in the surrounding river. This was investigated through experimentally installing car tyres into two rivers (one sand-bed and one gravel-bed river) and monitoring their effects on macroinvertebrates and fish. The macroinvertebrate communities inhabiting tyre surfaces in the sand-bed river were significantly more diverse and included more sensitive taxa than the surrounding river bed, whereas tyre surface communities were relatively impoverished in the gravel-bed river. In both rivers, tyres significantly affected macroinvertebrate communities in the surrounding river bed, which could be attributed to the influence of the tyres on local flow and sediment conditions, similar to the effects of natural structures like large wood and boulders. Some small fish (<15 cm long roach, chub, and dace) were also affected by tyres. They spent more time and fed more downstream of tyres than they did upstream, sheltering in the zone of slower flow velocity which may allow them to preserve energy. Other fish species and sizes were less frequently observed and did not seem to respond to the presence of tyres. This research is the first to show that anthropogenic litter can provide and create habitat in rivers. It suggests that, whilst litter should not be deliberately added to rivers, removing it could have the side effect of reducing local biodiversity, both for macroinvertebrates and fish, unless the habitat it provides is replaced by alternative materials.